Code PHASCOL for computation of space charge effects in the cyclotrons and synchrocyclotrons - Onischenko, L.M.; Samsonov, E.V. (Вопросы атомной науки и техники, 2001)
Development of the code is connected with the project of external injection into the JINR Phasotron. General description of the code PHASCOL intended for particle dynamic calculation that takes into account Coulomb interaction between cycling particles is given. A method of large particles is used in the code. Visual graphical possibilities of the Microsoft FPS 4.0 are applied for on-line representations of the main results of computations. Contemporary PC makes it possible to carry out in the course of 24 hrs the calculations of interaction of 2000 particles for 100 turns. Some first results of computation regarding to the JINR Phasotron with energy 680 MeV and four-sector cyclotron-injector with energy 5 MeV and beam currents up to 10 mA are presented.